Sensory Characterization and the Antioxidant Activity of Rooibos Tea - Dmowski, Przemysław; Szczygieł, Paulina (Studia Oeconomica Posnaniensia, 2017)
Rooibos tea is a herbal tea which comes from the endemic South African fynbos plant, Aspalathus linearis and it has a lot of medicinal properties. The most important characteristics of rooibos are its antioxidant as well as antimutagenic/ antitumoral properties. In spite of the growing popularity of rooibos as a herbal tea in Poland, general tools to ensure effective quality assessment and the control of its sensory properties do not currently exist. This study was thus conducted to character-ize and identify the sensory attributes associated with the rooibos flavour; colour and mouth feel to generate a more comprehensive picture of what is frequently referred to the Polish consumer of rooibos tea as "typical" or "characteristic". The aim of this study was to find the sensory attributes of rooibos tea offered for retail sales on the Tri-city market and next to compare them with the total phenolic content, determined with the Folin-Ciocalteu reagent and antioxidant activity determined by using the DPPH reagent. The sensory quality (i.e. the colour, flavour, taste and mouth feel of the infu-sion) of 10 samples was evaluated by experts. The most frequently occurring descrip-tors were selected to compile a rooibos sensory lexicon of 15 flavour, taste, colour and mouth feel attributes. Rooibos samples contained a total amount of polyphenols from 34.38 mg GAE/100 ml to 145.23 mg GAE/100 ml. Antioxidant properties also were very different and varied from 64.82% to 96.54%. There was a substantial correlation between the phenolic content versus antioxidant activity (r = 0.857, p = 0.0015). The sensory analysis showed significant differences in rooibos tea in colour, flavour, taste and mouth feel attributes. Using the PCA analysis the products currently offered on the Tri-city market have been classified into two main quality groups. Most low-quality samples were associated with negative sensory attributes such as a hay/dried grass taste, and an astringent and bitter mouth feel, while higher-grade samples were generally associated with the "characteristic" rooibos attributes, i.e. honey, fruit and herbal-floral flavours, a sweet, caramel taste, clear colour and soft/smooth mouth feel. The statistically significant linear correlation between the results of the sensory analysis and total phenolic content was found.